Pergeseran Ideologi al-Ikhwân al-Muslimûn dari Islam Fundamentalis menjadi Islam Moderat - Nurul Huda (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2014)
The reform in Egypt was originally considered as the end of the Islamic political system and replaced by the democratic system. However, after H{izb al-H{urrîyah wa al-‘Adâlah (Freedom and Justice Party) in Egypt was able to win the election and wiped out two of the most strategic positions, i.e. the speakerman of parliament and the president, it should be admitted that the Islamic political system has never ceased. There is a new fact that the Arab nations, especially Egypt, began to accept the democratic system without having to necessarily remove the role of Islam from it. Collaboration and integration between Islam and democracy is what has been introduced in Egypt today. Islamic system of democracy which is introduced in Egypt becomes the new hallmark of the Islamic movement or more precisely what so-called moderate Islam. Al-Ikhwân al-Muslimûn (IM) is a religious organization that is worthy of being a representation of the moderate Islamic forces today. It has managed to get out of the mode of fanaticism and conservatism (fundamentalist) toward adaptive patterns of thought and compromise. This study focuses on the factors and measures of IM changes from fundamentalist Islam to moderate Islam. This study concludes that IM’s ideological changes were driven by several factors, such as the role of the figure, government’s treatment, social condition, and human resources organization.